2010
DOI: 10.1093/brain/awq237
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor β ligand: a novel treatment to enhance endogenous functional remyelination

Abstract: Demyelinating diseases, such as multiple sclerosis, are characterized by inflammatory demyelination and neurodegeneration of the central nervous system. Therapeutic strategies that induce effective neuroprotection and enhance intrinsic repair mechanisms are central goals for future therapy of multiple sclerosis. Oestrogens and oestrogen receptor ligands are promising treatments to prevent multiple sclerosis-induced neurodegeneration. In the present study we investigated the capacity of oestrogen receptor β lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
119
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 86 publications
(116 reference statements)
13
119
0
2
Order By: Relevance
“…Current immunologic treatments for RR-MS are known to have a modest effect in preventing accumulation of disability [22]. While safety concerns associated with long-term therapeutic use of sex hormones should be considered [5] our results support a potential benefice of such compounds or their derivatives in combination with currently available immunomodulatory agents for the disease [23]. Overall, our results and previous work suggest that MS women considering the use of OC should not base their decision on potential deleterious effects on their clinical course.…”
Section: P-valuesupporting
confidence: 52%
See 1 more Smart Citation
“…Current immunologic treatments for RR-MS are known to have a modest effect in preventing accumulation of disability [22]. While safety concerns associated with long-term therapeutic use of sex hormones should be considered [5] our results support a potential benefice of such compounds or their derivatives in combination with currently available immunomodulatory agents for the disease [23]. Overall, our results and previous work suggest that MS women considering the use of OC should not base their decision on potential deleterious effects on their clinical course.…”
Section: P-valuesupporting
confidence: 52%
“…This interpretation is supported by experimental and clinical data indicating that sex hormones may have protective effects on brain damage and repair mechanisms in these patients [3][4][5]. All oestrogens are not exactly alike [5,23]. Importantly and unlike 17β-oestradiol, the common oestrogen found in pills ethynil oestradiol [24,25] and progesterone [26] reduce the clinical severity of EAE when given after the onset of disease signs.…”
Section: P-valuementioning
confidence: 79%
“…While the protective effect of estriol treatment on MS appears to be mediated in part by anti‐inflammatory mechanisms (Gold et al., 2009; Soldan, Alvarez Retuerto, Sicotte, & Voskuhl, 2003; Voskuhl & Gold, 2012), this is not mutually exclusive of direct neuroprotective effects, as these have been shown in the MS model (Crawford et al., 2010; Kim et al., 2018; MacKenzie‐Graham et al., 2012; Spence et al., 2011). Together, preclinical data in EAE have shown that estriol is acting to decrease microglial activation, induce remyelination, and increase synaptic plasticity (Kim et al., 2018; Ziehn et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…'s laboratories (8)] was dissolved in 10% ethanol + 90% (vol/vol) Miglyol 812N (vehicle; Sasol) and administered s.c. daily at 5 mg/kg body weight. Control groups received (s.c.) either 0.04 mg/kg/d 17β-estradiol (E2) or 8 mg/kg/48 h DPN (4,10). Treatment was initiated at EAE postinduction day 0 (preEAE) or day 21 (post/peakEAE) and continued until day 40.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent work has demonstrated promising neuroprotective effects of the estrogen receptor (ER) β agonist 2,3-bis(4-hydroxyphenyl)propionitrile (DPN) (4,5). Although DPN, acting through ERβ, has a desirable palliative effect in EAE, it possesses only 70-fold binding selectivity for ERβ over ERα and lacks anti-inflammatory effects (6,7).…”
mentioning
confidence: 99%